Deportasi Anak-Anak Dalam Konflik Bersenjata Sebagai Kejahatan Hak Asasi Manusia - Papilaya, Juventhia Elvanri; Wattimena, Josina Augustina Yvonne; Peilouw, Johanis Steny Franco (PATTIMURA Law Study Review, 2024)
ABSTRACT: War crimes often occur against civilians, namely children who are illegally deported or illegally detained. Of course, it is very contrary to international legal rules. The problems in this writing include how to regulate deportation in international law. Apart from that, can the deportation of children in armed conflict be classified as a human rights crime. The method used is a normative juridical research method with a qualitative type of analysis with interpretative analysis and conceptually tends to be directed at finding, identifying, managing and analyzing legal materials to understand the meaning, significance and relevance. The objectives to be achieved point to the dramatic evolution and extensive codification of human rights law, so it can be said "that human rights law makes a major contribution to the law of state accountability". Thus, it can be argued that state responsibility law regarding losses suffered by foreigners, in this case children who are victims of deportation, and human rights law have a close and reciprocal relationship. In line with the development of law and human rights, the law of state responsibility regarding losses experienced.